Dihydromyricetin protects against cerebral ischemia/reperfusion injury via suppressing microglia-mediated neuroinflammation and activation of ERK1/2-CREB signaling pathway. (June 2017) - Zhao, Yafei; Wang, Panpan; Chen, Shuangshuang; Han, Chaojun; Yan, Qiuting; Zheng, Longtai; Jia, Jia; Ren, Zhaoxiang; Zhen, Xuechu
Highlights: Dihydromyricetin (DHM) protected against cerebral ischemia in mouse MCAO model. Dihydromyricetin (DHM) suppressed microglia-mediated neuroinflammation. Dihydromyricetin (DHM) activated neuronal ERK-CREB-Bcl-2 signaling pathway. Abstract: Dihydromyricetin (DHM), a natural flavonoid compound extracted from the fruit Ampelopsis grossedentata, exerts various pharmacological effects. We explored the neuroprotective effects of DHM following cerebral ischemia. Male ICR mice were intraperitoneally injected with DHM for 7 days. Post-ischemic neurological deficits were evaluated with behavioral tests. Mice brain tissues were harvested for infarction analysis, immunohistochemistry. The production of pro-inflammatory mediators in microglial cells were assessed by qPCR and ELISA. Neuroprotective effects of DHM were assessed in HT22 neuronal cells subjected to oxygen-glucose deprivation (OGD)/reoxygenation. DHM reduced the activation of microglia, protected HT22 neurons against OGD-induced injury and promoted functional recovery following middle cerebral artery occlusion (MCAO). Mechanistically, DHM reduced release of pro-inflammatory mediators from microglia. In addition, DHM suppressed caspase-3 cleavage and upregulated CREB, Bcl-2 and phosphorylation of ERK1/2 in HT22 cells. Our study suggested that DHM protects against cerebral ischemia by suppressing microglial neuroinflammation and activating neuronal ERK-CREB-Bcl-2 signaling pathway.